Pandemic one health clones of Escherichia coli and Klebsiella pneumoniae producing CTX-M-14, CTX-M-27, CTX-M-55 and CTX-M-65 ESβLs among companion animals in northern Ecuador - Gonzales-Zubiate, Fernando A.; Tambor, José Humberto M.; Valencia-Bacca, Juan; Villota-Burbano, María Fernanda; Cardenas-Arias, Adriana; Esposito, Fernanda; Moura, Quézia; Fuga, Bruna; Sano, Elder; Pariona, Jesus G. M.; Jacome, Mishell Poleth Ortiz; Lincopan, Nilton (Frontiers in Cellular and Infection Microbiology, 2025)
From a One Health perspective, dogs and cats have begun to be recognized as important reservoirs for clinically significant multidrug-resistant bacterial pathogens. In this study, we investigated the occurrence and genomic features of ESβL producing Enterobacterales isolated from dogs, in the province of Imbabura, Ecuador. We identified four isolates expressing ESβLs from healthy and diseased animals. In this regard, two Escherichia coli strains producing CTX-M-55-like or CTX-M-65 ESβLs belonged to the international ST10 and ST162, whereas two Klebsiella pneumoniae producing CTX-M-14 or CTX-M-27 belonged to ST35 and ST661. Phylogenomic analysis clustered (95-105 SNP differences) CTX-M-55/ST10 E. coli from companion animal with food and human E. coli strains of ST10 isolated in 2016, in Australia and Cambodia, respectively; whereas CTX-M-27-positive K. pneumoniae ST661 was clustered (201-216 SNP differences) with human strains identified in Italy, in 2013 and 2017, respectively. In summary, we report the presence and genomic data of global human-associated clones of CTX-M-producing E. coli and K. pneumoniae in dogs, in Ecuador. The implementation of a national epidemiological surveillance program is necessary to establish future strategies to control the dissemination of antibiotic-resistant priority pathogens using a One Health approach.